Physical therapy in infants and preschool children with burns: retrospective descriptive study - Takino, Mikelini Ayumi; Itakussu, Edna Yukimi; Trelha, Celita Salmaso; Valenciano, Paola Janeiro; Fujisawa, Dirce Shizuko (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Burns are traumatic injuries that occur due to external events, and particularities of pediatric patients make it more serious condition. Physical therapy is essential to the recovery of children victims of burns and it should be started early during hospitalization. Objective: Define initial and final physical therapy care in children victims of burns, during the period of hospitalization, in a Burn Treatment Centers (BTC). Methods: Retrospective and descriptive study by means of gathering information in medical records of children victims of burns, convenience sample, consisted of patients in the 0-6 age group, that were interned in BTC of University Hospital/ UEL, from January 2011 to February 2014. Results: Data from 102 medical records were collected, physical therapy was realized in 94 (92.1%) cases, being respiratory physical therapy, placements, motor physical therapy, orthosis indication and orientation. In the first, second, last but one and last sessions, the most used breathing techniques were clearence maneuvers; the general placements was the most used; during motor physical therapy, the gait /walking and orientation were used with more frequency in last assistance. Conclusion: The initial physical therapy emphasizes the clearence maneuvers for prevention and treatment of respiratory complications that threaten the survival of the patient. The activities focused on functionality were adressed throughout the hospital stay, especially in the final stage. The physical therapy sessions progressed from passive techniques to active, according to the evolution of patients